Isolation of high-quality RNA from plant seeds - Mishko, Alisa; Sundyreva, Maria; Stepanov, Ilya; Efimenko, Sergey; Plotnikov, Vladimir; Nenko, Natalia (Biological Communications, 2021)
The apple (Malus domestica Borkh.) is one of the major fruit tree crops, but it hasn’t been well-studied as a breeding object for molecular investigations. It is important to develop reliable and rapid methods that allow the preparation of plant material for future research. We introduce a quick and simple method for isolating high-quality RNA from lipid-rich apple seeds (M. domestica cv. Golden Delicious). Our method does not employ highly toxic reagents, because we exclude phenol, 2-mercaptoethanol and others. The chemical composition of the extraction buffer is simple and has a minimum level of toxicity. We showed that, in chaotropic conditions (i.e., with lithium chloride-urea), silica (SiO2) can bind with the lipids and RNA will remain in the solution. The extracted RNA was of high quality and we successfully used it for synthesizing cDNA and RT-PCR. The protocol developed by us can be useful for researchers working with RNA extraction from plant seeds.